2017
DOI: 10.1177/2473011417695254
|View full text |Cite
|
Sign up to set email alerts
|

Most Readmissions Following Ankle Fracture Surgery Are Unrelated to Surgical Site Issues

Abstract: Background: Ankle fracture surgeries are generally safe and effective procedures; however, as quality-based reimbursement models are increasingly affected by postoperative readmission, we aimed to determine the causes and risk factors for readmission following ankle fracture surgery. Methods: Ankle fracture cases were identified from the prospectively collected American College of Surgeons National Surgical Quality Improvement Program from 2013 to 2014. Demographics, comorbidities, and fracture characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…This finding is consistent with prior studies that have demonstrated a similar comorbidity profile in the overall COVID patient population [26][27][28]. Additionally, the rate of comorbidities observed among COVID-negative patients in the current study is in accordance with prior ankle fracture cohort studies [29].…”
Section: Plos Onesupporting
confidence: 93%
“…This finding is consistent with prior studies that have demonstrated a similar comorbidity profile in the overall COVID patient population [26][27][28]. Additionally, the rate of comorbidities observed among COVID-negative patients in the current study is in accordance with prior ankle fracture cohort studies [29].…”
Section: Plos Onesupporting
confidence: 93%
“…16 Although no studies to our knowledge have examined the overlap of the current unplanned readmission metric with surgical quality, a few studies have attempted to estimate the number of unplanned readmissions that are potentially associated with the index surgical procedure. 1 , 17 , 18 , 19 , 20 , 21 We found that 71.6% of unplanned readmissions were associated with the index surgical procedure. Rosen and colleagues estimated a smaller number (ie, 42%) that were deemed “clinically related.” 17 Another recent study in an English population found that only 53% of unplanned readmissions were “surgical readmissions” associated with the index hip replacement or knee arthroscopy.…”
Section: Discussionmentioning
confidence: 71%
“…16 Although no studies to our knowledge have examined the overlap of the current unplanned readmission metric with surgical quality, a few studies have attempted to estimate the number of unplanned readmissions that are potentially associated with the index surgical procedure. 1,[17][18][19][20][21] We found that 71.6% of unplanned readmissions were associated with the index surgical procedure.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, even promptly surgically treated, a certain proportion of patients would be compromised by the unfavourable outcome, and surgical site infection (SSI) was an important cause 5 . It was reported that 24.1% of the unplanned readmissions were related to SSI 6 . In addition, SSI significantly prolonged the hospitalisation stay by 6 to 12 days and increased the medical care costs 7 .…”
Section: Introductionmentioning
confidence: 99%